Pengaruh Model Value Clarification Technique (VCT) terhadap Penalaran Moral Siswa Kelas V Sekolah Dasar - Pratiwi, Dita Eriyanti; Sutarno; M. Imron Rosyadi (Program Studi Pendidikan Guru Sekolah Dasar, Fakultas Keguruan dan Ilmu Pendidikan Univers, 2024)
The purpose of this study was to determine the effect of the Value Clarification Technique model on the moral reasoning of fifth-grade elementary school students. The study was quantitative with a Quasi-Experimental Research approach and a Nonequivalent Control Group Design. The results showed an average pre-test score of 62.86 for the experimental class and an average post-test score of 81.67 for the experimental class. The average pre-test score of 62.86 for the control class and an average post-test score of 72.14 for the control class. The results of the t-test using an independent sample t-test showed a significance level (2-tailed) of 0.000 < 0.05, thus rejecting Ho.